Induced systemic resistance -like responses elicited by rhizobia - Tonelli, Maria Laura (2020)
Rhizobia are soil bacteria that engage into a mutualistic symbiosis with plants and benefit the host by fixing atmospheric N. In addition, rhizobia can be considered as biocontrol agents, contributing to plant health through direct inhibition of a wide range of pathogens. More recently, it became evident that rhizobial invasion of plant roots can also trigger an increased systemic resistance state in the host, a process resembling the Induced Systemic Resistance (ISR) mechanism. However, this indirect biocontrol property of rhizobia was relatively less explored. Scope: In this review article, we present an overview of the current knowledge of ISR -like responses induced by rhizobia, considering general characteristics of this phenomenon, discussing the molecular pathways leading to this response and highlighting potential links between ISR -like responses and the nodulation signaling pathway. Conclusions: A more detailed knowledge of these responses can result in development of biotechnological tools for sustainable crop production, through optimization of the systemic protective effect conferred by rhizobia.